2003
DOI: 10.1109/tcapt.2003.821694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modifications to the nickel/gold surface finish on assembly quality and attachment reliability of a plastic ball grid array (peer review version)

Abstract: Electrolytic and electroless Ni/Au are common pad surface finishes on area array (BGA or CSP) packages and printed wiring boards (PWB). The electroless nickel/immersion gold (ENIG) process often is implemented when there is insufficient space to allow bussing for the more common electrolytic Ni/Au plating. The ENIG process continues to be used despite evidence that it may cause catastrophic, brittle, interfacial solder joint fractures. In this investigation a plastic ball grid array (PBGA) test vehicle is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The amount of phosphorus needs to be controlled, depending on the plating process, to eliminate the possibility of black pad. 19 Elemental analysis was conducted using an energy dispersive x-ray (EDX). The layer between the solder and the copper above the Ni layer was found to be phosphorus rich, indicating the possible presence of blackpad.…”
Section: Microvoids and Blackpadmentioning
confidence: 99%
“…The amount of phosphorus needs to be controlled, depending on the plating process, to eliminate the possibility of black pad. 19 Elemental analysis was conducted using an energy dispersive x-ray (EDX). The layer between the solder and the copper above the Ni layer was found to be phosphorus rich, indicating the possible presence of blackpad.…”
Section: Microvoids and Blackpadmentioning
confidence: 99%
“…It has been reported that the growth rate of intermetallic compounds is lower in the electrolytic Ni/solder and electroless Ni-P/solder systems than that in the Cu/solder system [15][16][17]. Previous studies also indicated that electrolytic Ni plating had a higher solder joint reliability than electroless Ni plating [16,18,19]. In addition, a gold layer, plated on the Ni layer of the metallized pads, not only improves wettability but also increases oxidation resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate Pd(P) layer prevents the Ni(P) layer from being attacked by the Au plating bath; thus, galvanic hypercorrosion of the Ni(P) layer (generally termed ''black pads'') can be significantly reduced. [6][7][8][9][10] The Au and Pd(P) finishes are customarily deposited within a range of 0.05 lm to 0.3 lm (thickness) in realistic applications of the Au/Pd(P)/ Ni(P) surface finish. 11 The influence of the Pd(P) thickness on the soldering reaction between the Sn-3Ag-0.5Cu alloy and the trilayer structure [i.e., Au/Pd(P)/Ni(P)] has recently been examined by Ho et al 12 The reaction refers to a liquid-solid reaction in which the Sn-3Ag-0.5Cu alloy is a liquid but the Au/Pd(P)/Ni(P) trilayer is solid.…”
Section: Introductionmentioning
confidence: 99%